Identifying the proper mix of growth-seeking strategies for Spanish SMEs: An analysis during times of economic boom and crisis - Diana Benito-Osorio; Alberto Colino-Fernández; Luis Ángel Guerras-Martín; José Ángel Zúñiga-Vicente (Small Business International Review)
This study explores the potential effects of different combinations of growth-seeking strategies on performance in SMEs during long times of economic boom and crisis. Our hypotheses are tested on a representative sample of Spanish SMEs between 1994 and 2014. During these years Spain suffered one of the periods of greatest economic stability/growth in recent years (1994-2008), followed immediately by a period of severe crisis (2009-2014). Using dynamic panel data models, our findings reveal that four combinations exhibit a positive and statistically significant effect on performance in times of economic boom: a related product strategy combined with low, moderate, or high levels of internationalization, and an unrelated one combined with a moderate level of internationalization. Meanwhile, we find only two combinations with a positive impact on SME performance in times of crisis: a related product strategy combined with low and moderate levels of internationalization, respectively